Development of interactive pop-up book learning media for human circulatory system material to increase high school students' interest in learning - Rahmi Siregar; Rohani Rohani (Inovasi Kurikulum, 2025)
This research aims to create a learning media in the form of a pop-up book that is applied to the content of the human circulatory system, which meets the requirements of validity, practicality, and effectiveness, and can increase students' interest in learning. The method used is Research and Development (R&D) with a 4D model, which consists of Define, Design, Develop, and Disseminate, but in this study, it is only up to the Develop stage. This study involved 33 students of grade XI Science 1 and a biology teacher at SMAS Cerdas Murni. Data was collected using validation sheets, practicality questionnaires for teachers and students, student learning interest questionnaires, and pretest and posttest questions. The validation results show that this media is highly valid, as validated by media and material experts. The practicality test showed efficient responses from teachers and students. The effectiveness of the media can be seen from the N-Gain score, indicating a high level of effectiveness, and the results of the student learning interest questionnaire show a very high level of interest. Based on these findings, this pop-up book is considered suitable as a learning tool because it meets the standards of validity, practicality, and effectiveness. In addition, this media also helps students understand the human circulatory system and grow their interest in learning biology.   Abstrak Penelitian ini memiliki tujuan untuk menciptakan media pembelajaran berbentuk pop-up book yang diterapkan untuk konten sistem peredaran darah manusia, yang memenuhi syarat validitas, praktikalitas, dan efektivitas, serta dapat meningkatkan minat peserta didik dalam belajar. Metode yang digunakan adalah Riset dan Pengembangan (R&D) dengan model 4D, yang terdiri dari Define, Design, Develop, dan Disseminate, tetapi dalam penelitian ini hanya sampai tahap Develop. Penelitian ini melibatkan 33 peserta didik kelas XI IPA 1 dan seorang guru Biologi di SMAS Cerdas Murni. Data dikumpulkan menggunakan lembar validasi, angket kepraktisan untuk guru dan peserta didik, angket minat belajar peserta didik, serta soal pretest dan posttest. Hasil validasi menunjukkan media ini sangat valid, dari ahli media dan ahli materi. Uji kepraktisan memperlihatkan tanggapan yang sangat praktis dari guru dan peserta didik. Efektivitas media terlihat dari skor N-Gain menunjukkan kategori tinggi dan hasil angket minat belajar peserta didik menunjukkan kategori sangat tinggi. Berdasarkan temuan tersebut, pop-up book ini dinilai cocok sebagai alat pembelajaran karena memenuhi standar validitas, kepraktisan, dan efektivitas. Selain itu, media ini turut membantu peserta didik dalam memahami sistem peredaran darah manusia dan menumbuhkan minat mereka untuk belajar Biologi. Kata Kunci: minat belajar peserta didik; pop-up book; sistem peredaran darah manusia